Laying hen manure in anaerobic Co-Digestion with glycerin containing different glycerol and impurity levels - Schwingel, Alice Watte; Amorim Orrico, Ana Carolina; Lucas Junior, Jorge de [UNESP]; Previdelli Orrico Junior, Marco Antonio; Aspilcueta Borquis, Rusbel Raul; Fava, Aldo Felipe (Elsevier B.V., 2019)
Biodiesel has arisen as a promising option of renewable fuel to minimize the impacts caused by fossil fuels. However, its production process generates high amounts of crude glycerin as a residue, which is considered low-quality commercially due to its low glycerol content. In order to add value to this byproduct, some production plants employ a purification process. Nonetheless, aiming to cut down costs with this purification step, many researches have been seeking treatments that use glycerin with lower purity, such as anaerobic co-digestion with another residue of complementary composition so as to balance the digestion medium and increase energy yield. During recycling, glycerin goes from an environmental liability to a sustainable financial asset by being transformed into cleaner energy, i.e., biogas. This research was carried out to assess the influence of glycerol content in glycerin containing the same impurities at three proportions (40% (G40), 60% (G60), and 80% (G80)), and to add them to the process at different glycerol levels (0, 1, 2, 3, and 4%) in the total solids (TS) of the affluents prepared with laying hen manure. No interaction was found between glycerin type and glycerol content regarding biogas and methane productions as well as reductions in TS and volatile solids (VS). Adding 2.5% glycerol led to the highest specific biogas production (1654.1 L kg(-1) VS added) while adding 2.6% yielded the maximum specific production of methane (1058.9 L kg(-1) VS added), i.e., glycerol increased methane generation by over 36% when compared with the treatment with no glycerin. Consequently, greater reductions in TS (60.97%) and VS (73.6%) were observed with ideal addition levels of 2.2 and 2.4% glycerol. Adding 2.1% glycerol using G40 resulted in the greatest reduction (55.4%) in chemical oxygen demand (COD) whereas such reduction was by 50.4 and 50.5% for G60 and G80 when 2.6% glycerol were added. With that in mind, and in face of the high costs of purification, G40 can be recommended with addition of 2.6% glycerol to TS to improve co-digestion with laying hen manure and generate energy that returns to poultry and biodiesel production systems. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Batch digestion; Biodiesel waste; Glycerin purity level; Methane production